Assessment of Natural Fruit Ripening and Fruit Quality of Three Elite Durian Cultivars for Overland Export - Wiangsamut, Bancha; Wiangsamut, Maria Evangeline Loyola (Trends in Sciences, 2023)
The study aimed to assess the natural fruit ripening duration, fruit quality, and consumer preference of 3 elite durian cultivars-‘Monthong’, ‘Musang King’, and ‘Ocee’-after harvest. From the day of harvest at maturity stage until the second day of the fresh fruits emitted aroma; ‘Monthong’ took 9 days for full ripening measured by the natural fruit ripening duration value significantly (p < 0.05) longer by 4 days than of ‘Musang King’ and ‘Ocee’. This value indicated that the longer ripening duration, the longer storage life was. The flesh weight, percentage of flesh weight, and flesh thickness most significantly influenced fruit quality. ‘Monthong’ had significantly higher flesh weight, percentage of flesh weight, and thicker flesh (p < 0.05) than ‘Musang King’ and ‘Ocee’. A questionnaire and interview guide were used to compare the sensory qualities (flesh smell and flesh taste) of the durian cultivars by 50 Thai consumers through smelling (mild, moderate, strong) and eating the flesh. Consumer preference was determined by eating the flesh and smelling each cultivar by the same 50 consumers and then chose the durian cultivar they mostly prefer. Consequently, consumers mostly preferred ‘Monthong’ (54 %) over ‘Musang King’ (28 %) and ‘Ocee’ (18 %) due to its mild aroma, mildly sweet taste, crispy but soft golden-yellow flesh. In conclusion, the significantly longer natural fruit ripening duration (or long storage life) of ‘Monthong’ plus its higher flesh weight, higher percentage of flesh weight, more flesh thickness, and consumers’ high preference are good indicators of its export quality-suitable for shipping fresh overland especially to China, top importer of Thailand. ‘Musang King’ and ‘Ocee’ had short ripening duration (or short storage life); ergo, poor export quality. Shipping by land, sea, and air, including packaging technology development, should then be studied further for the benefit of export market. HIGHLIGHTS The natural fruit ripening duration of ‘Monthong’ cultivar was significantly longer than ‘Musang King’ and ‘Ocee’ The longer storage life of ‘Monthong’ cultivar, due to its higher flesh weight, percentage of flesh weight, and flesh thickness, is a good indicator of an export quality suitable for shipping fresh fruit overland By means of smelling and eating the durian flesh by 50 Thai consumers, ‘Monthong’ was recorded to be the most preferred cultivar due to its mild aroma, mildly sweet taste, crispy outer but soft inner and golden-yellow colored flesh GRAPHICAL ABSTRACT